Neuropsychological effects and cognitive deficits associated with exposure to mercury and arsenic in children and adolescents of the Mojana region, Colombia (2023)
The present study aims to explore the neuropsychological performance and exposure to mercury (Hg) and arsenic (As) in Colombian children and adolescents considering biomarkers in hair and blood. The total sample consisted of 70 participants from the Mojana region, Colombia. A neuropsychological evaluation protocol was used, consisting of 11 internationally recognized tests, with evidence of national validation and use for measurement in neurotoxicology contexts. A 57.1% of the sample presented levels above the reference value according to the USEPA, the WHO, and the ATSDR for total mercury in hair (HgH), blood mercury (HgB), and/or blood arsenic (AsB). The mean values reported for HgH were 1.76 ± 3.1 μg/g (95% CI 1.02–2.50) with ranges between 0.23 and 17.20; for HgB: 4.11 ± 5.93 μg/l (CI 2.69–5.52), ranging between 0.25 and 25.80, and for AsB: 1.96 ± 2.73 (CI 1.31–2.61) ranging between 0.50 and 15.50. In the comparison of groups in relation to the level of exposure, a significant difference was found (p < 0.05) for the subtest The Boston Naming Test (BNT). Correlation analyses found, on the one hand, significant negative relationships in tests integrated within the verbal (CVB) and executive function (EF) components as well as evidence of positive relationships in the manifestation of errors in their performance with the levels of Hg and/or As transformed by biomarker (Log10). In the linear regression analyses it was found that for each increase in the concentration of HgH, HgB, and AsB it is estimated that, both for the models with and without data adjustment, there is a loss of scores in integrated measures within the CVB and EF for the transformed levels of HgH, HgB, and AsB; and an increase in the reported errors in their processing within these functions. According to these results, exposure to mercury and/or arsenic is related with performance in verbal neuropsychological skills and executive functioning.